2013
DOI: 10.1590/s1808-16572013000200005
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da dose e exposição à terra de diatomácea de diferentes insetos em milho armazenado

Abstract: Sitophilus zeamais e Tribolium castaneum são importantes insetos-pragas de grãos armazenados e seus danos correspondem a aproximadamente 25% das perdas na pós-colheita do Brasil. Entre as formas de controle destaca-se o uso de pós-inertes. Sendo assim, o objetivo deste trabalho foi avaliar a mortalidade de adultos de S. zeamais e T. castaneum com uso de terra de diatomácea (TD) em diferentes dosagens e períodos de exposição. Os tratamentos com terra de diatomácea foram: 1.000 e 2.000 g.t-1 e controle (sem apli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…(biochemical oxygen demand) chamber at 25 ± 3 ºC, with RU (relative air humidity) of 70 ± 10% and photophase of 12 h. The evaluations of susceptibility were performed 24 and 48 h after the treatments. Insects that did no move for two minutes were considered as dead (Antunes et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…(biochemical oxygen demand) chamber at 25 ± 3 ºC, with RU (relative air humidity) of 70 ± 10% and photophase of 12 h. The evaluations of susceptibility were performed 24 and 48 h after the treatments. Insects that did no move for two minutes were considered as dead (Antunes et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Pinto (2008), reported satisfactory mortality rates applying Diatomaceous Earth on three beetle species. Antunes et al (2013) performed another study with beetles and found positive results. Nwaubani et al (2014) and Kavallieratos et al (2015) corroborate the potential of Diatomaceous Earth for pest control proposed by the previous authors.…”
Section: Discussionmentioning
confidence: 99%
“…Treated corn grains were then infested with 10 unsexed adults of S. zeamais with 10 to 14 days of age, arranged in each replicate and maintained in a BOD (Biochemical oxygen demand) chamber, at temperature of 25 ± 3 ºC, humidity of 70 ± 10% and photophase of 12 h. The number of live insects was evaluated from the first to the 29th day after treatment. The number of live insects in each dish was quantified, and the insects that did not move for 2 min were considered as dead (Antunes et al, 2013).…”
Section: Methodsmentioning
confidence: 99%